2009
DOI: 10.1016/j.jsat.2008.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of depression and substance use among individuals with alcohol use disorders

Abstract: The relationships of depression with alcohol and drug use and impairment were examined. Additional analyses were conducted to examine moderators of these associations. Empirical reports on adults with alcohol abuse or dependence published in English in peer-reviewed journals since 1986 that contained data on depression and substance use variable(s) were obtained using a systematic search. The search yielded 74 studies including 58 reports from clinical venues, 10 that were community-based, and 6 with subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
193
1
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(229 citation statements)
references
References 126 publications
21
193
1
7
Order By: Relevance
“…This is a significant gap in the rehabilitation literature, given that alcohol use disorders are associated with increased mental and physical morbidity [15,16] which may result in impairments that could interfere with the ability to be physically active.…”
mentioning
confidence: 99%
“…This is a significant gap in the rehabilitation literature, given that alcohol use disorders are associated with increased mental and physical morbidity [15,16] which may result in impairments that could interfere with the ability to be physically active.…”
mentioning
confidence: 99%
“…It seems, also after a vast survey of relevant literature that analyses of relations between craving and perceived depression/anxiety are relatively very rare, especially in the framework of longitudinal, time points approach. Yet some of the studies addressed perceived depression/anxiety as a significant predictor of alcohol relapse, as well as the relation between perceived depression/anxiety and drinking, which is strongly mediated by alcohol craving (Conner et al, 2009). The craving module of the combined behavioural intervention (Witkiewitz et al, 2011) and Mindfulness-based relapse prevention were found to weaken the relation between perceived depression/anxiety and heavy drinking by fostering greater decreases in craving during treatment (Witkiewitz & Bowen, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of depression co-occurrence has been found to range from 24%-48% in alcohol dependent men and women respectively, and ranges from 50-70% in clinical samples [71], but following detoxification and abstinence this substantially reduces [72]. Although the recommendation [4,8] is to wait until the patient is 3-4 weeks abstinent from alcohol to reassess mood and need for treatment, both conditions often need to be addressed concurrently.…”
Section: Depression and Alcohol Dependencementioning
confidence: 99%